(untitled) (Iranian Journal of Kidney Diseases, 2020)
Familial mediterranean fever (FMF) is an autosomal recessive auto-inflammatory disorder, which could lead to secondary (AA) amyloidosis. Anakinra is an IL-1 receptor blocker and a treatment option for patients with FMF. There is no reported rejection episode associated with the use of Anakinra in the literature. A fortynine years old woman with a history of kidney transplantation is described here. Anakinra was initiated in the patients whose FMF attacks were exacerbated, and the inflammation could not be controlled under the colchicine treatment. After eight months of follow up under Anakinra treatment, a moderate but persistent increase in serum creatinine level was observed. Allograft biopsy was compatible with acute T cell-mediated rejection with BANFF type 2A. Data on the use of Anakinra in KTRs is limited. Antidrug- antibodies or hapten induced T cell activation may facilitate late-onset acute T cell-mediated rejection in the patient who used Anakinra.